Penetapan Isbat Nikah bagi Perkawinan yang Tidak Terdaftar - Reski Apriliani Idris; Soekarno Aburarera; Zainuddin Zainuddin; Asriati Asriati (Qawanin Jurnal Ilmu Hukum, 2020)
Abstract This study aims to determine how the determination of marriage isbat for marriages that are not registered in the Religious Court. As well as to find out and describe the problems of judges in determining marriage cases for marriages that are not registered in the Religious Court. This study uses an empirical legal research method. It is a research method that examines the function of a law or rule in terms of its application in the scope of society. The results of this study indicate that according to the positive law Indonesia, the judges of the Religious Court who accept it the application for marriage isbat for unregistered marriages made by the applicant 1 and applicant 2 is correct that the petition of the applicant is in accordance with article 7 paragraph 2 and paragraph 3 letter e of the Islamic Law Compilation, in addition to the requirements and harmony in the marriage is also in accordance with the provisions of the law Islam so that automatically the marriage is in accordance with Article 2 paragraph 1, because the marriage is contrary to article 2 paragraph 2, then Rare is the marriage ceremony conducted by the applicant in accordance with the provisions applies. The recommendation of this research is that prospective brides who are about to carry out a marriage should register their marriage at the local Office of Religious Affairs so that the marriage has legal certainty and orderly population administration. Abstrak Penelitian ini bertujuan untuk Untuk mengetahui bagaimana penetapan isbat nikah bagi perkawinan yang tidak terdaftar di Pengadilan Agama. Serta untuk mengetahui dan mendeskripsikan problematika hakim dalam menetapkan kasus isbat nikah bagi perkawinan yang tidak terdaftar di Pengadilan Agama. Penelitian ini menggunakan metode penelitian hukum empiris, Merupakan metode penelitian yang meninjau fungsi dari suatu hukum atau aturan dalam hal penerapannya di ruang lingkup masyarakat. Hasil penelitian ini menunjukkan Menurut Hukum positif di Indonesia, pertimbangan hakim Pengadilan Agama yang menerima permohonan isbat nikah bagi perkawinan yang tidak terdaftar di lakukan pemohon 1 dan pemohon 2 sudah benar bahwa permohonan pemohon telah sesuai dengan pasal 7 ayat 2 dan ayat 3 huruf e Kompilasi Hukum Islam, selain itu juga syarat dan rukun dalam pernikahan tersebut juga telah sesuai dengan ketentuan hukum Islam sehingga secara otomatis pernikahan tersebut telah sesuai dengan pasal 2 ayat 1, karena pernikahan tersebut bertentangan dengan pasal 2 ayat 2 maka langka isbat nikah yang dilakukan pemohon telah sesui dengan ketentuan yang berlaku. Rekomendasi penelitian ini yaitu untuk calon mempelai yang akan melangsungkan pernikahan sebaiknya untuk mendaftarkan pernikahan di Kantor Urusan Agama setempat agar pernikahan memiliki kepastian hukum dan tertib administrasi kependudukan.